Coffee, tea and decaffeinated coffee in relation to hepatocellular carcinoma in a European population: Multicentre, prospective cohort study. Issue 8 (24th September 2014) - Bamia, Christina; Lagiou, Pagona; Jenab, Mazda; Trichopoulou, Antonia; Fedirko, Veronika; Aleksandrova, Krasimira; Pischon, Tobias; Overvad, Kim; Olsen, Anja; Tjønneland, Anne; Boutron‐Ruault, Marie‐Christine; Fagherazzi, Guy; et al.
<x xml:space="preserve">Abstract</x> Inverse associations of coffee and/or tea in relation to hepatocellular carcinoma (HCC) risk have been consistently identified in studies conducted mostly in Asia where consumption patterns of such beverages differ from Europe. In the European Prospective Investigation into Cancer and nutrition (EPIC), we identified 201 HCC cases among 486, 799 men/women, after a median follow‐up of 11 years. We calculated adjusted hazard ratios (HRs) for HCC incidence in relation to quintiles/categories of coffee/tea intakes. We found that increased coffee and tea intakes were consistently associated with lower HCC risk. The inverse associations were substantial, monotonic and statistically significant. Coffee consumers in the highest compared to the lowest quintile had lower HCC risk by 72% [HR: 0.28; 95% confidence intervals (CIs): 0.16–0.50, p‐trend < 0.001]. The corresponding association of tea with HCC risk was 0.41 (95% CI: 0.22–0.78, p‐trend = 0.003). There was no compelling evidence of heterogeneity of these associations across strata of important HCC risk factors, including hepatitis B or hepatitis C status (available in a nested case–control study). The inverse, monotonic associations of coffee intake with HCC were apparent for caffeinated (p‐trend = 0.009), but not decaffeinated (p‐trend = 0.45) coffee for which, however, data were available for a fraction of subjects. Results from this multicentre, European cohort study strengthen the existing evidence regarding the inverse association between coffee/tea and HCC risk. Given the apparent lack of heterogeneity of these associations by HCC risk factors and that coffee/tea are universal exposures, our results could have important implications for high HCC risk subjects.